Anatomic Considerations for Radical Retropubic Prostatectomy in an Achondroplastic Dwarf. (2009) - Gyomber, Dennis; Angus, David; Lawrentschuk, Nathan
Abstract : This is the first report of a radical retropubic prostatectomy (RRP) in an achondroplastic dwarf. We highlight the pelvic anatomy, precluding laparoscopic or robotic prostatectomy, and making open surgery extremely difficult. We review relevant literature regarding general, urological, and orthopedic abnormalities of achondroplasia (ACH) and present a clinical case. No reports of RRP in achondroplastic dwarfs exist, with only one case of an abandoned RRP due to similar pelvic anatomy in a patient with osteogenesis imperfecta. Significant lumbar lordosis found in ACH results in a short anteroposterior dimension, severely limiting access to the prostate. We present a case of a 62-year-old achondroplastic dwarf who had Gleason 3+4 disease on transrectal ultrasound-guided biopsy in four from 12 cores. Surgery was difficult due to narrow anteroposterior pelvic dimension, but achievable. Histological analysis revealed multifocal prostate cancer, with negative surgical margins and no extraprostatic extension. RRP in ACH patients, although possible, should be approached with caution due to the abnormal pelvic dimensions, and discussions regarding potential abandonment of surgery should be included during informed consent. This case highlights the preoperative use of computed tomography to assist in the surgical planning for patients with difficult pelvic anatomy.